Barriers and facilitators to hepatitis B birth dose vaccination: Perspectives from healthcare providers and pregnant women accessing antenatal care in Nigeria - Catherine Freeland; Florence Kanu; Yahaya Mohammed; Ugochukwu Uzoechina Nwokoro; Hardeep Sandhu; Hadley Ikwe; Belinda Uba; Adeyelu Asekun; Charles Akataobi; Adefisoye Adewole; Rhoda Fadahunsi; Margeret Wisdom; et al. (Public Library of Science (PLoS), 2023)
Nigeria is estimated to have the largest number of children worldwide, living with chronic hepatitis B virus (HBV) infection, the leading cause of liver cancer. Up to 90% of children infected at birth develop chronic HBV infection. A birth dose of the hepatitis B vaccine (HepB-BD) followed by at least two additional vaccine doses is recommended for prevention. This study assessed barriers and facilitators of HepB-BD administration and uptake, using structured interviews with healthcare providers and pregnant women in Adamawa and Enugu States, Nigeria. The Consolidated Framework for Implementation Sciences Research (CFIR) guided data collection and analysis. We interviewed 87 key informants (40 healthcare providers and 47 pregnant women) and created a codebook for data analysis. Codes were developed by reviewing the literature and reading a subsample of queries line-by-line. The overarching themes identified as barriers among healthcare providers were: the lack of hepatitis B knowledge, limited availability of HepB-BD to vaccination days only, misconceptions about HepB-BD vaccination, challenges in health facility staffing capacity, costs associated with vaccine transportation, and concerns related to vaccine wastage. Facilitators of timely HepB-BD vaccination included: vaccine availability, storage, and hospital births occurring during immunization days. Overarching themes identified as barriers among pregnant women were lack of hepatitis B knowledge, limited understanding of HepB-BD importance, and limited access to vaccines for births occurring outside of a health facility. Facilitators were high vaccine acceptance and willingness for their infants to receive HepB-BD if recommended by providers. Findings indicate the need for enhanced HepB-BD vaccination training for HCWs, educating pregnant women on HBV and the importance of timely HepB-BD, updating policies to enable HepB-BD administration within 24 hours of birth, expanding HepB-BD availability in public and private hospital maternity wards for all facility births, and outreach activities to reach home births.